Getting ready for Angular 2 what you need to know before you make the jump - Davis, Scott 1971- (O'Reilly, 2016)
"In this course you'll learn the various syntactical changes introduced in Angular 2 and also how the new Angular is componentsdriven and leverages features of the modern webs tack. Angular 2 also offers flexibility in terms of language choice, and this course will introduce two main development paths, one using TypeScript and another using ECMAScript 6. This course will also introduce tooling and libraries that will be important for your development environment when working with Angular 2. By the end of this course, you will have gained an understanding of the changes coming in Angular 2, the decision making behind these choices, and how to be prepared to make the jump when Angular 2 releases."--Resource description page.
Title from title screen (viewed April 14, 2016)
Keywords: AngularJS (Software framework); Software frameworks; Cadres d'applications (Informatique)